Haemoglobin mass in cyclists during stage racing - Schumacher, Y. O.; Pottgiesser, T.; Ahlgrim, C.; Ruthardt, S.; Dickhuth, H. H.; Roecker, K. (International Journal of Sports Medicine, 2008)
Haemoglobin mass is a main determinant of maximal oxygen uptake. Blood doping aims at increasing this variable. Limits for haematocrit and haemoglobin concentration are used as indicators of blood doping. However, these variables are measures of concentration, do not represent total haemoglobin mass and are altered by vascular volumes shifts. Direct estimation of haemoglobin mass could improve blood tests. It is unknown if physical exercise alters haemoglobin mass. The purpose of this study was to investigate the reaction of haemoglobin mass and other vascular compartments to heavy exercise in athletes. Haemoglobin mass and vascular compartments were evaluated using the optimised CO rebreathing method in 7 elite cyclists during a stage race. Simultaneously, haemoglobin concentration and haematocrit were analysed. Haemoglobin mass (pre-race 958 ± 123 g, end race 948 ± 106 g) and red cell volume did not change significantly over the study period, while plasma volume and blood volume tended to increase. Haematocrit (pre-race 44.1 ± 2.5 %, end race 40.9 ± 1.59 %) and haemoglobin concentration (pre race 15.8 ± 0.9 g/dl, end race 14.7 ± 0.7 g/dl) decreased. During the study, a plasma volume expansion as adaptation to prolonged exercise occurred. Haemoglobin concentration and haematocrit decreased accordingly, whereas haemoglobin mass remained stable. Haemoglobin mass might therefore be a suitable screening tool for blood manipulations.